A Fibromyxoid Stromal Response Is Associated With an Infiltrative Tumor Morphology, Perineural Invasion, and Lymph Node Metastasis in Squamous Cell Carcinoma of the Vulva. (September 2015) - Jeffus, Susanne K.; Gehlot, Ashita; Holthoff, Emily; Stone, Rebecca; Spencer, Horace; Kelly, Thomas; Post, Steven R.; Quick, Charles M.
Abstract : Patterns of invasion and stromal response are understudied in vulvar squamous cell carcinoma. The aim of this study was to explore whether histologic features such as an infiltrative pattern of invasion and fibromyxoid stromal response (FMX-SR) are meaningful prognostic factors. We reviewed 143 vulvar squamous cell carcinoma resections and correlated patterns of invasion and stromal response with patient age, ethnicity, depth of invasion, tumor size, perineural invasion (S100/AE1/3 stain), lymph node involvement (LNI), extranodal extension, margin status, pathologic stage, and recurrence. Univariate analyses of continuous variables were performed using t tests, whereas Pearson χ 2 tests were used for categorical variables. Logistic regression analyses examined the relationship between histopathologic characteristics and clinical outcomes. There was a statistically significant association between infiltrative tumors and an FMX-SR in comparison with noninfiltrative tumors ( P <0.001). Tumors with FMX-SR were significantly more deeply invasive ( P =0.0025) and more likely to have LNI ( P =0.0364), extranodal extension ( P =0.0227), and perineural invasion ( P =0.0011) compared with tumors without FMX-SR. For cases with negative surgical margins, the association between tumors with FMX-SR and LNI was significantly strengthened (odds ratio=4.73, P =0.0042), even after adjustments for age, race, and depth of invasion (odds ratio=4.34, P =0.0154). The presence of both FMX-SR and an infiltrative pattern of invasion in tumors with negative margins was significantly associated with LNI ( P =0.0235) and recurrence ( P =0.0124). These results suggest that interactions between nerve, tumor, and stromal cells play a role in tumor progression and represent additional prognostic factors that help stratify those patients at highest risk for LNI, extranodal extension, and recurrence.